2020
DOI: 10.1080/1331677x.2020.1771745
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulation, innovation quality and firms’ competitivity―Quasi-natural experiment based on China’s carbon emissions trading pilot

Abstract: In the study of the "Porter Hypothesis", scholars explored the impact of different forms of innovation on the firms' competitivity, but did not distinguish between innovations on the difference in patent quality. In addition, relevant research only regards innovation as a mediator between environmental regulation and competitivity, and doesn't take into account innovation induced by environmental regulation, can only promote competitivity under the constraints of environmental regulation. That is to say, envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…However, imperfect environmental regulation, i.e., alternate energy source subsidies, policy implementation lags, and strict carbon emission tax, promote green paradox by encouraging businesses to increase extraction levels, hence leading to higher GHG emissions (Wahab et al, 2021;Van der Werf & Di Maria, 2012). The existing literature suggests that environmental regulations and environmental technologies have a different impact on the carbon emissions in different countries (Bogusz & Howlett, 2008;Hu et al, 2020;Kalkuhl et al, 2012;Voigt et al, 2014). Hence, figuring out some effective environmental regulations in the developed economies such as OECD are important for achieving GHG reduction levels prescribed under various climate agreements, i.e., Kyoto protocol, Paris climate agreement.…”
Section: Environmental Taxes and Energy Use In Oecdmentioning
confidence: 99%
“…However, imperfect environmental regulation, i.e., alternate energy source subsidies, policy implementation lags, and strict carbon emission tax, promote green paradox by encouraging businesses to increase extraction levels, hence leading to higher GHG emissions (Wahab et al, 2021;Van der Werf & Di Maria, 2012). The existing literature suggests that environmental regulations and environmental technologies have a different impact on the carbon emissions in different countries (Bogusz & Howlett, 2008;Hu et al, 2020;Kalkuhl et al, 2012;Voigt et al, 2014). Hence, figuring out some effective environmental regulations in the developed economies such as OECD are important for achieving GHG reduction levels prescribed under various climate agreements, i.e., Kyoto protocol, Paris climate agreement.…”
Section: Environmental Taxes and Energy Use In Oecdmentioning
confidence: 99%
“…As a result, strengthening environmental regulation will make innovation play a greater role in saving energy consumption and reducing pollutant emissions. Meanwhile, Yao et al (2019) and Hu et al (2020) used Chinese listed companies as the sample and found that environmental regulations play a positive moderating role in the relationship between innovation and corporate value. However, the economic development of China is currently in the process of transforming from a factor-driven to innovation-driven mode .…”
Section: Panel Threshold Model Settingmentioning
confidence: 99%
“…Zeng et al (2021) proposed an extended synthetic control method with multiple units for evaluating the dynamic treatment effects on air quality improvement. Hu et al (2020) performed an analysis of environmental regulation, innovation quality, and firms' competitiveness in carbon emission trading. We will follow these studies to further evaluate both short-and long-term effects of marine sand regulation policies and protection of coastal structures and ecosystems.…”
Section: Discussionmentioning
confidence: 99%